2023
DOI: 10.1038/s41467-023-36056-4
|View full text |Cite
|
Sign up to set email alerts
|

A three-terminal magnetic thermal transistor

Abstract: Three-terminal thermal analogies to electrical transistors have been proposed for use in thermal amplification, thermal switching, or thermal logic, but have not yet been demonstrated experimentally. Here, we design and fabricate a three-terminal magnetic thermal transistor in which the gate temperature controls the source-drain heat flow by toggling the source-drain thermal conductance from ON to OFF. The centimeter-scale thermal transistor uses gate-temperature dependent magnetic forces to actuate motion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…Over the years, various thermal transistors based on near-field thermal radiation, [6] nonlinear phonon conduction in nanoscale systems, [7,8] nanoscale confined fluids, quantum electronic systems, [9][10][11][12][13] and Josephson junction between different superconductors [14,15] have been designed and some of them have been experimentally demonstrated. [16][17][18][19][20][21] In many cases, with the help of a suitably designed electromagnetic field, the thermal control functions can be realized more easily.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, various thermal transistors based on near-field thermal radiation, [6] nonlinear phonon conduction in nanoscale systems, [7,8] nanoscale confined fluids, quantum electronic systems, [9][10][11][12][13] and Josephson junction between different superconductors [14,15] have been designed and some of them have been experimentally demonstrated. [16][17][18][19][20][21] In many cases, with the help of a suitably designed electromagnetic field, the thermal control functions can be realized more easily.…”
Section: Introductionmentioning
confidence: 99%
“…As an example of the former, Wang and Li theoretically proposed thermal transistors, which modulate the heat transport by a heat input. , Very recently, Castelli et al . demonstrated such a thermal transistor, which utilizes paramagnetic/ferromagnetic switching of a magnet to mechanically control the heat conductance . As an example of the latter, Ben-Abdallah and Biehs theoretically proposed a thermal transistor, which modulates the thermal conductivity of the active material (VO 2 ) electrically .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Very recently, Castelli et al demonstrated such a thermal transistor, which utilizes paramagnetic/ferromagnetic switching of a magnet to mechanically control the heat conductance. 5 As an example of the latter, Ben-Abdallah and Biehs theoretically proposed a thermal transistor, which modulates the thermal conductivity of the active material (VO 2 ) electrically. 6 VO 2 shows an insulator-to-metal transition around 68 °C, and metallic VO 2 shows a large electrical conductivity (σ ∼ 10 4 S cm −1 ).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Organic thin film transistors (OTFTs) have sparked great interest owing to their high mechanical flexibility and low cost, and have shown great application prospects in active-matrix displays, [1][2][3][4][5][6][7][8][9] smart sensors, [10,11] and logic circuits. [12][13][14][15] Coplanar architecture (bottom-contact, BC) is the most promising device configuration for high-throughput production of high-density OTFTs, [16][17][18] because this architecture is well-compatible with photolithography technique without damaging organic semiconductors. However, coplanar OTFTs generally suffer from poor charge injection, so their performance is severely limited.…”
Section: Introductionmentioning
confidence: 99%